2014
DOI: 10.1007/s00429-014-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

Central connectivity of the chorda tympani afferent terminals in the rat rostral nucleus of the solitary tract

Abstract: The rostral nucleus of the solitary tract (rNST) receives gustatory input via chorda tympani (CT) afferents from the anterior two-thirds of the tongue and transmits it to higher brain regions. To help understand how the gustatory information is processed at the 1st relay nucleus of the brain stem, we investigated the central connectivity of the CT afferent terminals in the central subdivision of the rat rNST through retrograde labeling with horseradish peroxidase, immunogold staining for GABA, glycine, and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Sections were immunostained for GABA and glycine (Gly) by the postembedding immunogold staining method, as previously described from our laboratory (Paik et al, ; Park, Lee, Bae, & Bae, ). Briefly, the grids were treated for 15 min in 1% periodic acid, and for 10 min in 9% sodium periodate, transferred to tris‐buffered saline containing 0.1% triton X‐100 (TBST; pH 7.4) and incubated in 2% human serum albumin (HSA) in TBST for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were immunostained for GABA and glycine (Gly) by the postembedding immunogold staining method, as previously described from our laboratory (Paik et al, ; Park, Lee, Bae, & Bae, ). Briefly, the grids were treated for 15 min in 1% periodic acid, and for 10 min in 9% sodium periodate, transferred to tris‐buffered saline containing 0.1% triton X‐100 (TBST; pH 7.4) and incubated in 2% human serum albumin (HSA) in TBST for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…These antisera (a kind gift from professor O.P. Ottersen at the Center for Molecular Biology and Neuroscience, University of Oslo) have been extensively characterized (Takumi, Ramírez‐León, Laake, Rinvik, & Ottersen, ) and routinely used in our previous works (Bae et al, ; Paik et al, ; Park et al, , ). Their specificity was also confirmed on thin sections of “sandwiches” of rat brain macromolecule‐glutaraldehyde complexes of different amino acids, including GABA, glutamate, taurine, glycine, aspartate, glutamine, and none (Bae et al, ; Ottersen, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that the terminals of chorda tympani afferents, primarily an Aδ fiber, convey gustatory information from the anterior part of the tongue and make simple synaptic connections in the first relay nucleus, the rNST. This organization differs from that of the complex synaptic connections made by non-gustatory Aδ fibers in the trigeminal nuclei ( Alvarez et al, 1992 ; Park et al, 2016 ). However, less is yet known about the central connectivity of the glutamatergic rNST neurons in the PBN and RF.…”
Section: Introductionmentioning
confidence: 76%
“…The bouton volume, mitochondrial volume and active zone area of the VGLUT2+ boutons on the JC γ-motoneurons, all measures of synaptic strength, were uniformly small and similar to those of VGLUT1+ and VGLUT2+ boutons on the JO and JC α-motoneurons that originate from intrinsic premotoneurons [6], and different from those of VGLUT1+ boutons of the Vmes afferents [6] or primary sensory afferents, which are mostly large [6, 20, 21]. We interpret this to suggest that the glutamatergic input originating from intrinsic premotoneurons exerts a much weaker influence on the JC γ-motoneurons (as well as on JC and JO α-motoneurons) than glutamatergic input originating from proprioceptive primary afferents, and it may be involved in the fine regulation of isometric contraction of the JC muscles.…”
Section: Resultsmentioning
confidence: 99%